Medical Activity of the Church Organizational Units - Poniatowski, Michał (Prawo Kanoniczne, 2025)
The article presents an analysis of the medical activities of the church organizational units under the current Polish legal system, including the relationship thereof to the church’s public law. Following the framework of the article, the topic in question is presented relative to the Catholic Church’s organizational unit. First, due to the nature of these units, the normative guarantees of freedom to conduct this type of activity are discussed. These guarantees are later detailed with respect to the scope of the said type of activity. The article also contains an analysis of the pluralism of entities that are allowed to conduct such activity. The last part of the article embraces final conclusions.